An assessment of citizenship and democracy education curriculum in practice - Gömleksiz, Mehmet Nuri; Akyildiz, Salih (My University, 2012)
The aim of this study is to assess effectiveness of Citizenship and Democracy Education curriculum in 8th grade of elementary school in practice. For that aim, a 40-item Citizenship and Democracy Education Curriculum Scale was developed and used by the researchers. Study group of the research consisted of 465 teachers, who teach Citizenship and Democracy Education Course in Rize, Trabzon, Giresun, Ordu and Samsun cities. Data were analyzed in terms of city, gender, seniority, type of school graduated and branch variables. Mean scores, frequency, percent, independent groups t test, one way Anova, Kruskal Wallis H, Mann Whitney U and LSD tests were used to analyze the data. The findings proved that learning attainments, content, teaching-learning process and evaluation parts of the curriculum were effective in practice. Statistically significant difference was observed among teachers' opinions towards content of the curriculum in terms of seniority variable. It is recommended that the teachers should be provided inservice education for the content of the curriculum.
Vatandaşlik ve demokrasi e?itimi dersi ö?retim programinin uygulamadaki etkilili?inin de?erlendirilmesi
Keywords: Citizenship and Democracy Education Curriculum; Constructivism; Curriculum evaluation